Econometric analysis of the Colombian oil sector from the perspective of the market efficiency hypothesis [Análisis econométrico del sector petrolero colombiano desde la perspectiva de la hipótesis de eficiencia de mercado] (2017)
A study on the Market Efficiency Theory in its weak and semi-strong form, for oil companies listed on the Colombia Stock Exchange is done, considering the effect of WTI in these. The article shows that only profitability series of Ecopetrol can be considered as random walk through a further transformation using the WTI in the model, but in the other assets there is no Market Efficiency in its weak form. Stable models in mean and variance for assets and additional models including the performance of WTI as a variable within models of actions were found, showing signs of market efficiency in its semi-strong form. Since then it is not possible to demonstrate efficiency for all actions, for purposes of this paper concludes that the Colombian market presents anomalies.